Drivers and value tradeoffs of regional-scale adaptation in rural landscapes of central Europe - Brady Mattsson (Research Ideas and Outcomes, 2020)
Coupled human and natural systems exhibit complex interactions (e.g. feedback-loops) that are often poorly understood. Decision-makers from regional (e.g., state or provincial) scale environmental stewardship programs to international policy makers are often faced with uncertainties about future climatic and sociopolitical conditions (henceforth, system change) when supporting livelihoods and ecosystem services derived from lands and waters they oversee. Understanding how these system changes interact with adaptive decision-making processes toward stewardship of ecosystem services represents a considerable gap in knowledge. Adaptation, or iterative adjustment of management practices in response to or anticipation of system change, has been forwarded as a means of effective ecosystem stewardship. Furthermore, lack of clarity about value tradeoffs among competing program objectives (e.g., economics and aesthetics) often precludes development and implementation of adaptation. Although there have been several qualitative studies on regional to national adaptation, lacking is an empirical understanding of how the drivers and value tradeoffs associated with adaptation differ among regions and between related sectors spanning multiple countries. Diverse cultural heritages and political structures among regions of central Europe offer great opportunities for examining spatial patterns of limitations to regional-scale adaptation in forest and agricultural sectors. This project will develop a quantitative index of adaptation for examining hypotheses about patterns of rural adaptation within regions of nine countries in central Europe. Alternative hypotheses describe contrasting assumptions regarding geographic variation in the relative importance among drivers and objectives associated with adaptation. Predictions derived from these hypotheses will be examined through a survey instrument that gathers information from programs focused on rural stewardship. Survey data will be analyzed using a hierarchical Bayesian approach that accounts for biases and missing information often resulting from surveys. Interviews will be used to validate survey responses and receive feedback on inferences made from the analysis of the survey data. Placing findings within the context of existing adaptation literature and evaluating subtler patterns that emerge from the survey data will generate new hypotheses to be examined through future research. The research will be conducted at University of Natural Resources and Life Sciences (BOKU) in Vienna. The applicant Harald Vacik from the Institute of Silviculture at the Department of Forest and Soil Sciences has proven his expertise on the evaluation of natural resource management in the context of sustainability, biodiversity and climate change. The post docs Brady Mattsson, Pia Kieninger and the PhD student Werner Toth contribute with their experience in developing climate adaptation decision support systems and providing uncertainty analysis in environmental decision-making. The proposed study will be an important step in advancing knowledge about adaptation and the interplay between humans and nature in maintaining a sustainable supply of ecosystem goods and services. This novel research integrates multiple scientific disciplines (e.g., ecology, sociology, decision theory, statistics) and to generate an integrated index of adaptation.